Wind dynamics and leaf motion: Approaching the design of high-tech devices for energy harvesting for operation on plant leaves - Meder, Fabian; Naselli, Giovanna Adele; Mazzolai, Barbara (Frontiers in Plant Science, 2022)
High-tech sensors, energy harvesters, and robots are increasingly being developed for operation on plant leaves. This introduces an extra load which the leaf must withstand, often under further dynamic forces like wind. Here, we took the example of mechanical energy harvesters that consist of flat artificial “leaves” fixed on the petioles of N. oleander converting wind energy into electricity. We developed a combined experimental and computational approach to describe the static and dynamic mechanics of the natural and the artificial leaf individually and joint together in the typical energy harvesting configuration. The model, in which the leaves are torsional springs with flexible petioles and rigid lamina deforming under the effect of gravity and wind, enables to design the artificial device in terms of weight, flexibility, and dimensions based on the mechanical properties of the plant leaf. Moreover, it predicts the dynamic motions of the leaf-artificial leaf combination causing the mechanical-to-electrical energy conversion at a given wind speed. The computational results are validated in dynamic experiments measuring the electrical output of the plant-hybrid energy harvester. Our approach enables to design the artificial structure for damage-safe operation on leaves (avoiding overloading caused by the interaction between leaves and/or by the wind) and suggests how to improve the combined leaf oscillations affecting the energy harvesting performance. We furthermore discuss how the mathematical model could be extended in future works. In summary, this is a first approach to improve the adaptation of artificial devices to plants, advance their performance, and to counteract damage by mathematical modelling in the devices design phase.